MicroRNA-325-3p Targets Human Epididymis Protein 4 to Relieve Right Ventricular Fibrosis in Rats with Pulmonary Arterial Hypertension - Yi Tang; Xiaowei Huo; Junyu Liu; Yijin Tang; Min Zhang; Wenlin Xie; Zhaofen Zheng; Jin He; Jiayan Lian (Cardiovascular Therapeutics)
Background. Pulmonary arterial hypertension (PAH) usually causes right ventricular dysfunction, which is closely related to cardiac fibrosis. But cardiac fibrosis mechanism remains unclear. Our purpose was to explore microRNA-325-3p (miR-325-3p)/human epididymis protein 4’s (HE4) role in the occurrence and development of right ventricular fibrosis in PAH. Methods. The right ventricular fibrosis model of rats with PAH was constructed, and miR-325-3p was overexpressed to explore miR-325-3p’s effect on myocardial fibrosis in rats with PAH. Pearson correlation coefficient examined the correlation between HE4 and miR-325-3p. We separated and identified the primary rat myocardial fibroblasts from the heart tissue. Then, the Ang II-treated myocardial fibroblast fibrosis model was constructed. miR-325-3p mimics and si-HE4 and oe-HE4 cell lines were constructed to investigate miR-325-3p and HE4 effects on myocardial cell fibrosis. Then, we added PI3K inhibitor LY294002 to study the effects of HE4 in cell fibrosis by the PI3K/AKT pathway. Starbase was used to predict miR-325-3p and HE4 binding sites. Dual-luciferase reporter assay verified whether miR-325-3p and HE4 were targeted. Results. Overexpression of miR-325-3p alleviated myocardial fibrosis in rats with PAH. Pearson correlation coefficient showed that HE4 was negatively correlated with miR-325-3p expression. Starbase predicted that miR-325-3p had binding sites with HE4. Dual-luciferase reporter assay demonstrated that miR-325-3p targeted HE4. Overexpression of miR-325-3p downregulated HE4 and inhibited myocardial fibroblast fibrosis. HE4 knockdown inhibited myocardial fibroblast fibrosis. HE4 promoted myocardial fibroblast fibrosis and activated the PI3K/AKT pathway. In addition, HE4 affected myocardial fibroblast fibrosis through the PI3K/AKT pathway. Conclusions. miR-325-3p could target HE4 to relieve right ventricular fibrosis in rats with PAH. This study could provide new targets and strategies for right ventricular fibrosis in PAH.